"A man without money getting a sexual partner? It doesn't exist in our community": male partners' perspectives on transactional sexual relationships in Uganda and Eswatini. Issue 7 (1st July 2022) - Pulerwitz, J.; Valenzuela, C.; Gottert, A.; Siu, G.; Shabangu, P.; Mathur, S.
Abstract: Research on transactional sexual relationships has largely focused on women's perspectives. Better understanding the men's views—especially regarding relationships with adolescent girls and young women—can inform HIV prevention efforts. In 2017, 134 in-depth interviews were conducted with the male partners of girls and young women aged 19–47 years, 94 in Uganda and 40 in Eswatini. Respondents were recruited at venues such as bars where men and potential partners meet and through other young women. Most respondents believed that providing money/gifts was the way to establish relationships with women in their communities, a context that some found undesirable. Young women were mainly perceived as actively pursuing transactional sex for material goods, but respondents also described economically impoverished women who were manipulated into relationships. Men described conflict with longer term partners as a driver to seeking younger partners, who were more compliant. Transaction dominates the male partners of adolescent girls and young women's understanding of sexual relationships, and inequitable power dynamics are reinforced by seeking younger partners. However, some respondents' discontent with this dynamic suggests an opportunity for change. HIV prevention programmes should directly address the underlying drivers of transactional relationships (e.g. gender norms) and work with men who question the practice.